Święto w językowej świadomości Polaków i Rosjan - Orzechowska, Joanna (Studia Rossica Posnaniensia, 2016)
Linguistic awareness has been one of the research interests in both cognitive and cultural linguistics in recent years. Images of linguistic signs which originate as part of the linguistic awareness of representatives of various cultures and languages can differ considerably. There are many ways of distinguishing these differences, including semantic analysis and analysis of the connotations related to a given word. This article presents how the term holiday functions in the linguistic awareness of Poles and Russians.